2002
DOI: 10.1149/1.1448186
|View full text |Cite
|
Sign up to set email alerts
|

Control of the (111) Orientation in Copper Interconnection Layer

Abstract: This paper describes various parameters affecting to the ͑111͒ orientation in electroplating copper conductive layers. Control of this orientation is important because resistivity, stress, adhesion strength, and electromigration resistance of copper layer are affected largely by this orientation. This orientation cannot be controlled with varying electroplating conditions but can be controlled by the orientation of the copper seed layer used as substrate. That is, the ͑111͒ orientation of electroplating copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…2,8 However, seed layers deposited on the more usual Ta/TaN and Ta barrier layers have been highly stressed. 2,5 Much lower stress can be obtained in seed layers deposited on TaSiN barriers. 4 Nevertheless, more detailed analysis of the deposition of lower resistivity copper layers is required.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,8 However, seed layers deposited on the more usual Ta/TaN and Ta barrier layers have been highly stressed. 2,5 Much lower stress can be obtained in seed layers deposited on TaSiN barriers. 4 Nevertheless, more detailed analysis of the deposition of lower resistivity copper layers is required.…”
Section: Resultsmentioning
confidence: 99%
“…4 Thus, barrier layers of TaN and Ta/TaN have been used extensively in conventional copper interconnection systems, although the copper layer formed on these barriers is highly stressed. 5,6 Because the copper interconnection layer must be surrounded by a thick barrier layer of Ta/TaN, for instance, Ͼ15 nm thick, a layer with a smaller net cross-sectional area has been manufactured. In practice, higher sheet resistance interconnects have been used in present very largescale integrateds ͑VLSIs͒.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies of copper electrodeposition employing the conventional sulphate bath have shown that these metal films perform lower conductivity and higher internal stress, compared to those of metallurgical samples [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Grain size of the electroplating Cu is determined mainly by the stress and orientation of the Cu seed layer employed for electroplating. 4 To deposit or fabricate a low resistance Cu interconnection layer, correlation of the resistivity with many other parameters must be obtained. In this paper, We describe the effect of stress and grain growth in the seed and electroplated layer on the resistivity in the interconnection layer.…”
mentioning
confidence: 99%